A Retrospective Cohort Study on the Clinical Course of Patients With Moderate-Type COVID-19 - Liao, Xiaohua; Lv, Xin; Song, Cheng; Jiang, Mao; He, Ronglin; Han, Yuanyuan; Li, Mengyu; Zhang, Yan; Jiang, Yupeng; Meng, Jie (Frontiers in Public Health, 2021)
Background: A large number of people got moderate type COVID-19 around the world. However, at present there were no researches about the clinical course of patients with moderate type COVID-19. The study described the clinical course of moderate type patients with COVID-19 from Wuhan City and Yiyang City, and explored relevant factors to the length of hospitalization and symptoms relief. Methods: The study analyzed the clinical course of 107 moderate type patients with COVID-19 from the outbreak area (Wuhan) and the imported area (Yiyang), and used automatic linear modeling and multivariate linear regression analysis to explore the relevant factors to the length of hospitalization and symptoms relief. Furthermore, we created a scoring system to value the length of hospitalization and symptoms relief. Results: Lymphopenia, elevated C-reactive protein, increased LDH, bilateral lung GGO(ground glass opacity) and lung consolidation were more likely to appear in ordinary inpatients with moderate type COVID-19 from Wuhan(P<0.05), compared to infected medical staffs from Wuhan and ordinary inpatients with moderate type COVID-19 from Yiyang. Meanwhile, the length of hospitalization and symptoms relief were longer in ordinary patients with moderate type COVID-19 from Wuhan(P<0.05). Onset of symptom to admission, ESR, leucocytes count and bilateral lung GGO were linearly related to the length of hospitalization(P<0.05); onset of symptom to admission, leucocytes count, bilateral lung GGO and lung consolidation were linearly related to the length of symptoms relief(P<0.05). By using the scoring system, we found that the time of hospitalization and symptoms relief was lengthened along with the scores increasing. Conclusions: This study described the clinical course of patients with moderate type COVID-19, and found that ordinary patients with moderate type COVID-19 in outbreak areas were more serious and needed stronger treatment and longer treatment time. Onset of symptom to admission, ESR, leucocytes count and bilateral lung GGO can be effective predictors of the length of hospitalization. And onset of symptom to admission, leucocytes count, bilateral lung GGO and lung consolidation can be effective predictors of the length of symptoms relief. Most importantly, we have offered a scoring system, which would contribute to the diagnosis and treatment of COVID-19.